COVID-19: In the Eye of the Cytokine Storm - de la Rica, Roberto; Borges, Marcio; Gonzalez-Freire, Marta (Frontiers in Immunology, 2020)
The dysregulated release of cytokines has been identified as one of the key factors behind poorer outcomes in COVID-19. This ‘cytokine storm ‘produces an excessive inflammatory and immune response, especially in the lungs, leading to acute respiratory distress (ARDS), pulmonary edema and multi-organ failure. Alleviating this inflammatory state is crucial to improve prognosis. Pro-inflammatory factors play a central role in COVID-19 severity, especially in patients with comorbidities In these situations, an overactive, untreated immune response can be deadly, suggesting that mortality in COVID-19 cases is likely due to this virally driven hyperinflammation. Administering immunomodulators has not yielded conclusive improvements in other pathologies characterized by dysregulated inflammation such as sepsis, SARS-CoV-1 and MERS. The success of these drugs at reducing COVID-19-driven inflammation is still anecdotal and comes with serious risks. It is also imperative to screen the elderly for risk factors that predispose them to severe COVID-19. Immunosenescence and comorbidities should be taken into consideration. In this review, we summarize the latest data available about the role of the cytokine storm in COVID-19 disease severity as well as potential therapeutic approaches to ameliorate it. We also examine the role of inflammation in other diseases often comorbid with COVID-19, such as aging, sepsis, and pulmonary disorders. Finally, we identify gaps in our knowledge and suggest priorities for future research aimed at stratifying patients according to risk as well as personalizing therapies in the context of COVID19-driven hyperinflammation